2021
DOI: 10.3390/bioengineering8020017
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Collagen Jungle: The Biomedical Potential of Fiber Organization in Cancer

Abstract: Recent research has highlighted the importance of key tumor microenvironment features, notably the collagen-rich extracellular matrix (ECM) in characterizing tumor invasion and progression. This led to great interest from both basic researchers and clinicians, including pathologists, to include collagen fiber evaluation as part of the investigation of cancer development and progression. Fibrillar collagen is the most abundant in the normal extracellular matrix, and was revealed to be upregulated in many cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 129 publications
1
55
1
Order By: Relevance
“…In the present study, we focused on COL4A5. COL4A has six different isoforms, the chains of which form heterotrimers to construct a complex collagen network in the basement membrane [20]. Comparison of the expression of the six isoforms revealed COL4A5 and COL4A6 as showing the highest expression in intramuscular fat relative to subcutaneous fat (Figure 5b), with this confirmed by qPCR (Figure S4).…”
Section: Expression Analysis Of the Col4 Isoformmentioning
confidence: 76%
See 2 more Smart Citations
“…In the present study, we focused on COL4A5. COL4A has six different isoforms, the chains of which form heterotrimers to construct a complex collagen network in the basement membrane [20]. Comparison of the expression of the six isoforms revealed COL4A5 and COL4A6 as showing the highest expression in intramuscular fat relative to subcutaneous fat (Figure 5b), with this confirmed by qPCR (Figure S4).…”
Section: Expression Analysis Of the Col4 Isoformmentioning
confidence: 76%
“…Therefore, it is suggested that TGF-β/SMAD pathway-mediated promotion of gene transcription might underly intramuscular fat formation in Japanese Black cattle. Furthermore, ITGA6 and ITGB1, the subunits of integrin α6β1 that specifically bind to the COL4A5 heterotrimer [20], were increased in intramuscular fat. The expression of cell migration factors CXCL5, FGF9, and FGF13, was also increased in intramuscular fat tissue (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying alignment of fibrillar features in biological images has gained wide interest as a possible biomarker in disease aetiology and progression (Ouellette et al, 2021). While tools are available for this aim (Püspöki et al, 2016; .…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes in cytoskeletal architecture can be seen in reconstituted protein systems (Falzone et al, 2013;Linsmeier et al, 2016). Additionally, the extracellular matrix (ECM) also has an inherent capacity to align in different tissues or pathologies, such as cancer (Ouellette et al, 2021) or tissue fibrosis (Park et al, 2020;Mascharak et al, 2021), which is thought to alter the ECM network mechanical properties. These examples illustrate the variety of environments where alignment of features reveals important biological properties.…”
Section: Introductionmentioning
confidence: 91%